Stereotypes Against Female Online Ojek Drivers in Surakarta - Shinta Rosalina; Nurhadi Nurhadi; Yuhastina Yuhastina (HUMANISMA : Journal of Gender Studies, 2021)
This study investigated the stereotypes of female online motorcycle taxi drivers, who pinned the stereotype of female online motorcycle taxi drivers, and why the stereotype of female online motorcycle taxi drivers in Surakarta emerged. This study used a qualitative method with a phenomenological approach. Sources of data used were primary data sources and secondary data sources—the data collected by interviews and observations. The informant retrieval technique used was snowball sampling and purposive sampling. This study indicated that (1) The stereotype of online motorcycle taxi drivers arises from a sub-culture in a society where men are closely related to masculine characteristics while women are feminine. So, working as a driver in a society closely related to masculine people creates stereotypes for women. (2) In the process, the stereotype of female online motorcycle taxi drivers appeared in most of the people who interacted with them, such as customers, fellow online motorcycle taxi drivers, and their families. (3) The reason for the emergence of a stereotype among female motorcycle taxi drivers is that women's driving proficiency is not the same as men's. In general, women who drive on a man are considered less common in some societies. Especially if the female drivers still receive orders at night, some community members and fellow male drivers consider it to be precarious and endangering to women. Penelitian ini bertujuan untuk mengetahui bagaimana stereotip driver ojek online perempuan, siapa yang menyematkan stereotip driver ojek online perempuan dan mengapa stereotip driver ojek online perempuan di Kota Surakarta muncul. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Sumber data yang digunakan adalah sumber data primer dan sumber data sekunder. Hasil dari penelitian ini menunjukkan bahwa (1) Stereotip pada driver ojek online muncul dari adanya sub budaya dalam masyarakat bahwa laki-laki erat dengan sifat maskulin sedangkan perempuan dengan sifat feminim. Sehingga, ranah pekerjaan sebagai driver yang di masyarakat erat dengan kaum maskulin membuat munculnya stereotip pada perempuan. (2) Dalam prosesnya stereotip terhadap driver ojek online perempuan muncul pada sebagian besar orang yang berinteraksi dengannya seperti customer, rekan sesama driver ojek online dan keluarga. (3) Alasan munculnya sebuah stereotip pada driver ojek perempuan berkaitan dengan kemahiran dalam mengemudi perempuan tidak sama dengan kaum laki-laki. Secara umum perempuan yang memboncengkan seorang laki-laki dianggap kurang lazim bagi sebagian masyarakat.Terlebih jika di malam haridriver perempuan yang masih gadis masih menerima orderan hal tersebut dianggap oleh sebagian masyarakat maupun dari teman sesama driver laki-laki sangat beresiko dan membahayakan diri perempuan.